Directions of developing regional governance - Шеденов, У. (Journal of Economic Research & Business Administration, 2017)
In this work for the sustainable economic development of the regions of Kazakhstan are presented in theory the principles of improving governance and practical recommendations ehkon social trends. Also provided are methods of optimization and development through the identification and analysis of regional management glavnyx problems in Kazakhstan. For Kazaxstana state regional policy aimed at vyrovnivanie trends in socio-economic development it is important from a strategic point of view. Sustainable razvitik national economy is not possible without improving the living conditions in the country problematicheskix regionax. The current economic area of the Republic oxvatyvaet different regions xarakterizuyuschiesya social, economic, environmental, special problems. The aim of the study is problematic regions. These are regions with low economic potential and lags behind the national average figure is several times due to a number of reasons. Inputs are also regions with inconsistent production and A poor infrastructure. Such regions are in need of government assistance motivating their development. Therefore, on the verge of global economic trends for Kazaxstana main task, it needs to be addressed a neutralizing negative consequences for the regions and creating necessary conditions for their development, increase the positive result.